2019
DOI: 10.1038/s41392-019-0061-x
|View full text |Cite
|
Sign up to set email alerts
|

miR-124/VAMP3 is a novel therapeutic target for mitigation of surgical trauma-induced microglial activation

Abstract: Activation of microglia and the subsequently elevated inflammatory cytokine release in the brain during surgery predispose individuals to cognitive dysfunction, also known as postoperative cognitive dysfunction (POCD). miR-124 is one of the most abundant microRNAs in the brain that regulates microglial function. Elucidating the role of miR-124 in microglial activation in the context of surgery may therefore promote understanding of as well as therapeutic development for post-surgical disorders involving microg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 61 publications
(62 reference statements)
0
35
0
Order By: Relevance
“…In addition, Tatsumi et al suggest that ROCK activation is necessary for P38 MAPK phosphorylation in the development of chronic pain [31]. Furthermore, it was also reported by Wilkerson et al that AM1241 produced profound anti-allodynia with a corresponding decrease in phosphorylation of p38MAPK immunoreactive cells and their protein levels in nonneuropathic pain rats [34]. Intrathecal injection of the p38MAPK antagonist SB203580 decreased NF-ÎşB, resulting 20 in pain relief in neuropathic pain rats [11,36].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, Tatsumi et al suggest that ROCK activation is necessary for P38 MAPK phosphorylation in the development of chronic pain [31]. Furthermore, it was also reported by Wilkerson et al that AM1241 produced profound anti-allodynia with a corresponding decrease in phosphorylation of p38MAPK immunoreactive cells and their protein levels in nonneuropathic pain rats [34]. Intrathecal injection of the p38MAPK antagonist SB203580 decreased NF-ÎşB, resulting 20 in pain relief in neuropathic pain rats [11,36].…”
Section: Discussionmentioning
confidence: 88%
“…More recent studies convince that miR-124 is one of the most abundant microRNAs in the brain and spinal cord that regulates microglial function[17,18,34,35]. The decreased expression of miR-124 was reported in cancer pain, carrageenan-induced and peripheral nerve injury-induced chronic As shown inFig.6A, treatment with AM1241 reduced this CCI-induced mechanical allodynia (P<0.05, compare with CCI rats) and the effect was reversed by the AM630 (P<0.05, compare with AM1241-treated CCI rats).…”
mentioning
confidence: 99%
“… 28 VAMP3 is a crucial therapeutic target for microglial activation by surgical trauma. 29 VAMP3 is involved in endothelial weibel‐palade bodies in exocytosis. 30 VAMP3 mediates the disturbed secretion of flow‐induced endothelial microRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Karthikeyan et al demonstrated how microglial cells exposed to GBM conditioned-medium exhibited a greater ability to migrate and attributed this phenotype to decreased levels of miR-146a and resulting upregulation of its target SMAD family member 4 (SMAD4), a critical node involved in the activation of the TGF-β pathway and genes such as matrix metallopeptidase 9 (MMP9), which facilitates tumor cell invasion [81]. A reverse cross-talk, between miR-124-3p-containing microglial exosomes and neuronal cells, was demonstrated by Li et al in a mouse model of brain injury [82]; this brain-specific miRNA is downregulated both in activated microglia and in GBM cells [43,83,84]. Li et al demonstrated that temozolomide (TMZ)-resistant GBM cells trigger the M2-polarization of microglial cells thanks to the long-noncoding RNA SNHG15 (upregulated in GBM cells), and its associated molecular axis made up of miR-627 (tumor suppressor, normally downregulated in GBM) and CDK6 (oncoprotein, directly targeted by miR-627) [85].…”
Section: Mirnas Mediate the Cross-talk Between Gbm And Microglia Cellsmentioning
confidence: 99%